ASUPAN ZAT GIZI MAKRO PADA PENDERITA DEMAM TYPOID DI RSUD MAROS - Ridha Sufiani Ismail; Rudy Hartono; Chaerunnimah Chaerunnimah (Politeknik Kesehatan Makassar, 2017)
Typhoid fever is a deases in small intestine and could cause continous symptoms, that was generated by salmonella thyposa. Knowing macro nutrition intake for typhoid fever patients in Makassar City Hospital. The study is acase study with observationa approach, patient’s nutrition intake data obtained 24 hours food recall form and the data was analized using Food Material Needs List. Macro nutrition intake in first and second day in recall averaged, is known at 2239.15 kcal energy (77,1%) which categorized moderate, energy’s intake were close to standard amount that recomended. 75.3 gr (103.85) proteins, which categorized normal and protein’s intake was fulfill standard amount that was recomended. 86.05 gr (117 %) fats which categorized very excessive, fat’s intake was exceeded standard amount that was recomended. 294.65 gr (54 %) carbohydrate which categorized deficient, and was not meet the standard amount that was recommended. Medical diagnosis Febris Pro Ev. patients nutrition status was normal nutrition status from IMT 23.89 kg/m2 result. Intervention that was given to the patient in from stomach diet (tender food) and education about diet advice based on patient’s condition and needs was given. Key Word : Macro nnutrition intake, Nutrition status , Thypoid fever